2014
DOI: 10.4103/0253-7613.135957
|View full text |Cite
|
Sign up to set email alerts
|

Survey of knowledge-attitude-practice concerning insulin use in adult diabetic patients in eastern India

Abstract: Objectives:The study was conducted to assess knowledge, attitude, and practice regarding insulin use among diabetic patients in tertiary care hospitals.Materials and Methods:Type 1 and 2 diabetic patients, aged 18 years and above, attending the Medicine/Endocrinology out-patient department or admitted as in-patients in three hospitals in and around Kolkata were enrolled. A pretested structured questionnaire comprising of 51 items was administered through face-to-face interview. Responses from 385 subjects were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 12 publications
3
17
1
Order By: Relevance
“…However, studies with migrant British South Asians have found this group to have poor knowledge and understanding of the seriousness of diabetes [ 9 ], lower perceived awareness of its complications, poor knowledge about diet, and poor adherence to medication [ 10 ] resulting in poor diabetes outcomes [ 11 ]. Similar findings in terms of knowledge and attitudes of diabetes have also been reported in South Asians residing in the East [ 12 , 13 ].…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, studies with migrant British South Asians have found this group to have poor knowledge and understanding of the seriousness of diabetes [ 9 ], lower perceived awareness of its complications, poor knowledge about diet, and poor adherence to medication [ 10 ] resulting in poor diabetes outcomes [ 11 ]. Similar findings in terms of knowledge and attitudes of diabetes have also been reported in South Asians residing in the East [ 12 , 13 ].…”
Section: Introductionsupporting
confidence: 85%
“…Low levels of literacy were also a common barrier to diabetes management [ 13 ]. Choudhury et al (2014) [ 12 ] used a KAP survey to assess insulin use in 358 diabetes patients in tertiary care hospitals in India. Higher educational and socioeconomic status was associated with better understanding of insulin use and complications related to diabetes.…”
Section: Discussionmentioning
confidence: 99%
“… Chan [ 92 ] 2014 The patient participants are insulin naïve. Choudhury [ 93 ] 2014 It was not possible to differentiate data specific to insulin treated T2DM. Cramer & Pugh [ 94 ] 2005 The focus is on insulin prescriptions issued and not on perceptions or experiences.…”
Section: Resultsmentioning
confidence: 99%
“…The result obtained in this study, have showed statistically significant differences in the area of attitude scores of case group after the educational intervention, which is consistent with other conducted studies. [ 23 28 ] The results showed that the patients’ mean field performance of case group has improved after the intervention. Mean paired t -test showed that self care behavior scores in the intervention group had significant difference, but not in the control group.…”
Section: Discussionmentioning
confidence: 99%